THE EFFECT OF SELF-EFFICACY AND SELF-REGULATED LEARNING ON ACADEMIC PROCRASTINATION AMONG STUDENTS AT STATE JUNIOR HIGH SCHOOL 6 IN MAKASSAR - Karmila Suud; Abdul Saman; Abdullah Pandang (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the influence of self-efficacy and self-regulated learning on students’ academic procrastination at SMP Negeri 6 Makassar. The research employed a quantitative approach with an ex post facto design. The research population consisted of students from grades VII, VIII, and IX, with a total sample of 104 students selected using a saturated sampling technique. Data were collected through questionnaires, interviews, and documentation. Data analysis included classical assumption tests (normality, multicollinearity, and heteroscedasticity tests) and multiple regression analysis. The results indicate that students’ self-efficacy levels were predominantly in the moderate (51.0%) and high (49.0%) categories, while self-regulated learning was mostly in the high category (60.6%). Academic procrastination was largely categorized as low (51.0%). Regression analysis revealed that self-efficacy had a negative and significant effect on academic procrastination (p < 0.05). Similarly, self-regulated learning also had a negative and significant effect on academic procrastination (p < 0.05). Simultaneously, self-efficacy and self-regulated learning showed a significant influence on students’ academic procrastination. This study concludes that higher levels of self-efficacy and self-regulated learning are associated with lower levels of academic procrastination. These findings highlight the importance of strengthening students’ self-beliefs and self-regulation skills through guidance and counseling services to reduce academic procrastination in schools.